Hubungan Kelekatan Orangtua-Anak Dengan Kepercayaan Diri Santri Pondok Pesantren Di Surakarta - Monica, Anggita Eva; , Dra. Partini, M.Si (2017)
Students are expected when entering boarding school have the confidence, because the attitude of self-confidence that can shape students become independent, however, the fact that occurred showed a lack of confidence which can be seen from the problems which the students fail to recognize its role in the social environment that causes feeling rejected and did not understand the ability itself. One factor affecting confidence are parents who give more attention so that the occurrence of stickiness. The purpose of this research is (1)to know the correlation of attachment with confidence, (2) to know the level of attachment of parent at boarding school student, (3) to know the level of confidence in boarding school student, (4) effective contribution of parent attachment to Self confidanceboarding school student. Research subjects used Cluster random sampling, from 7 boarding schools elected 2 boarding school consisting of 8 classes totalling 142 subject. Hypothesis proposed that there is a positive correlation between parents-child attachment with self confidance student. Analysis technique using product moment correlation test. Obtained correlation coefficient value of 0.477 with significance p = 0.000 (p <0.01) which means there is a very significant positive the correlation parental-child attachment with self confidance student. Parent-child attachment level belongs to the height and the level of confidence of students classified as high. The effective contribution of attachment to self-confidence is 22.75% and there are 77.25% of variables that influence confidence among others peers and community factors. Keywords: attachment, self-confidance, Boarding school student